Risk on Consumer Finance Company Personal Loans: Discussion - Shay, Robert P. (Journal of Finance, 1977)
Robert P. Shay, Risk on Consumer Finance Company Personal Loans: Discussion, The Journal of Finance, Vol. 32, No. 2, Papers and Proceedings of the Thirty-Fifth Annual Meeting of the American Finance Association, Atlantic City, New Jersey, September 16-18, 1976 (May, 1977), pp. 622-625